One old and two new species of phyllanthus from northwestern south america (1944)
Phyllanthus lacerilobus sp. nov. / Phyllanthus Haughtii. sp. nov. / Phyllanthus popayanensis Pax in Engl. Bot. Jahrb. 26: 503. 1899.